Sustentabilidad Y Desarrollo Tecnológico: A La Búsqueda De La “Herramienta Justa” - Claudio Fabian Guevara; Gabriela Scartascini Spadaro (European Scientific Journal, ESJ, 2017)
Technological development can be defined as a set of activities such as research, production, and distribution that facilitates the ready availability of new products and services to the society. It is a fundamental pillar of the model of hegemonic life on the planet. There are few questions about the direction of scientific and technical innovation. It however rests on the hands of private corporations which are not subject to public scrutiny. The omnipresent growth of technology poses deep dilemmas because it is not only polluting the environment, but is also questioning the very necessity of the existence of human beings. An analysis of the orientation of technological development is timely and necessary. This paper analyzes, from the perspective of sustainability, the design of technological development in terms of its environmental consequences and its impact on the society. Are all technologies beneficial? Is the design of a hyperindustrial, electronic and cybernetic society the only possible technological development? What criteria should we apply to choose between different paths? To open a debate on these questions, a conceptual framework on technological development is proposed from four perspectives: Purposes of technology; Scales and rates of expansion; Social participation in its design; Strategies related to the environment. The notion of "just tool" (Ivan Illich, 1974) is proposed as a principle of discussion.